Teaching Kids Fruit and Veggie Benefits through Media Book Design - Cahyadi, Eky; Aryani, Dewi Isma (Equilibrium: Jurnal Pendidikan, 2025)
A healthy lifestyle is a habit that can be instilled from an early age. Consuming vegetables and fruits as a healthy lifestyle has many benefits for health and fitness. Vegetables and fruits play an important role in helping the growth and development of early childhood. This study is part of the design process carried out through a descriptive quantitative method approach. From the data collection carried out, it was found that early childhood has an interest in interactive and attractive media. One of the media in question is a book design with educational and interactive content. Book design media can be one solution that can anticipate the low interest of early childhood in Indonesia in consuming vegetables and fruits. Interactive educational books are the right media in providing knowledge and insight to early childhood because in addition to being informative, they are also equipped with useful interactive aspects. Introduction to shapes, colors, and information about vegetables and fruits can be packaged comprehensively in interactive book media. The ultimate goal of this interactive educational book is to increase the knowledge, insight, and interest of early childhood, especially 6-10 years old, in vegetables and fruits as part of their healthy lifestyle.